(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
Fertility of BRIS soil was evaluated for growth performance of Hibiscus sabdariffa.L (Roselle) and to determine on the potential of Sesbania grandiflora as green manure for improvement of BRIS soil fertility. Growth performance of Hibiscus sabdariffa.L (Roselle) was determined by using three different media; BRIS soil, BRIS soil with compost and BRIS soil with green manure under two different light conditions (30% and 50%). The growth performance analysis of Roselle was carried out in the study to determine the effects on height of stem, number of leaves, stem diameter and biomass production (fresh and dry weight) of Roselle plants. The result showed that, the highest performance of stem height of Roselle was in BRIS soil with compost under 30% light intensity, while the best performance in term of number of leaves was BRIS soil with compost under 50% light intensity. In term of stem diameter, the highest value was in BRIS soil with compost under 50% light intensity. The highest performance of biomass production (fresh and dry weight) of roots, stems and fruit was treatment BRIS soil with compost under 50% light intensity. Based on statistical analysis using non-parametric method, the result indicated that there was significant different in the comparison of media BRIS soil and BRIS soil with compost under two different light conditions (30% and 50%). However, there was no significant different in comparison of media BRIS soil and BRIS soil with green manure. BRIS soil with compost showed the highest potential for growth performance of Roselle. In conclusion, compost is the best treatment that suitable for BRIS soil as it improves the fertility and structure of BRIS soil. Similarly, the light condition of 50% was better than 30% as sufficient amount of light is important for photosynthesis process and for growth and yield of plants.